AB0091 Surface phenotype of circulating platelets is altered in patients with rheumatoid arthritis. (15th June 2017) - Yasuoka, H; Yoshimoto, K; Yamaoka, K; Takeuchi, T
Abstract : Background: Rheumatoid arthritis (RA) is a connective tissue disease and characterized with multiple synovitis. However, pathogenesis of RA and systemic characteristic of RA is still under the investigation (1). Platelets distribute systemically through blood circulation and classically contribute to hemostasis physiologically (2). On the other hand, platelets can contribute to disease process by producing humoral factors such as cytokines or growth factors (3). Also, platelets have surface molecules not only associated with hemostasis but with other functional properties. Thus, these molecules can trigger the activation of other cells by cell-to-cell contact (4). Objectives: To examine the association between characteristics of phenotype of circulating platelets based on the expression of surface molecules and clinical characteristics of RA and to seek the possibility as novel biomarkers. Methods: Eight patients with RA were involved and 9 with scleroderma and 13 healthy controls were used as controls in this study. Surface expression of CD62P (P-selectin), membrane-bound TGF (transforming growth factor)-beta, CD147 (emmprin), CD142 (tissue factor), CD31 (platelet endothelial cell adhesion molecule (PECAM)-1) on CD41+CD45-CD14- platelets was examined using flow cytometry. Comparison between two groups was by non-parametric Mann-Whitney U-test. Clinical parameters at blood drawing were retrospectively obtained from clinical records, and correlation between proportion of platelet subsets and clinical parameters were examined. Results: Proportion of CD62P+ activated platelets were higher in both RA and SSc compared to HC (P<0.0005, P<0.0002, respectively). Interestingly, CD147+ platelets were significantly higher in RA (P<0.0004), whereas not only proportion of CD147+ platelets but that of TGF-beta+ platelets were higher in SSc compared to healthy controls (P<0.0001, respectively). In patients with RA, proportion of CD62P+ activated platelets was correlated with inflammatory markers such as CRP and ESR and markers for disease activity such as SDAI (P<0.05, respectively) and these proportion were decreased after treatment (P<0.03). Conclusions: In patients with RA, proportion of CD62P+ and CD147+ platelets were increased compared to healthy controls. Furthermore, phenotype of platelets of RA was altered compared to SSc. Interestingly, proportion of CD62P+ platelet is associated with the inflammatory markers and disease activity of RA. These results suggest that platelets reflect disease process of RA and could be utilized as novel biomarkers. References: Smolen JS et al. Rheumatoid arthritis. Lancet 388: 2023–2038, 2016. Bizzozero G et al. Sur un nouvel element morphologue du sang chez les mammiferes et son importance dans la thombose et dans la coagulation. Arch Ital Biol 1:1–5, 1882. Morrell CN et al. Emerging roles for platelets as immune and inflammatory cells. Blood 123:2759–2767, 2014. Van Velzen JF et al. Multicolor flow cytometry for evaluation of platelet surface antigens and activation markers. Thromb Res 130:92–8, 2012. Disclosure of Interest: None declared